2012
DOI: 10.1364/oe.20.021612
|View full text |Cite
|
Sign up to set email alerts
|

Generation and transmission of 854 Gb/s real-time 16QAM coherent optical OFDM signals over 400 km SSMF with preamble-less reception

Abstract: This paper presents a real-time, coherent optical OFDM transmitter based on a field programmable gate array implementation. The transmitter uses 16QAM mapping and runs at 28 GSa/s achieving a data rate of 85.4 Gb/s on a single polarization. A cyclic prefix of 25% of the symbol duration is added enabling dispersion-tolerant transmission over up to 400 km of SSMF. This is the first transmission experiment performed with a real-time OFDM transmitter running at data rates higher than 40 Gb/s. A key aspect of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…For instance, the constant modulus algorithm (CMA) [15] is frequently used for polarization demultiplexing. In [2] and [13], it has been shown to also work for recovering frequency and timing information. The CMA cost function is defined by (16) is used as a cost function instead of the one for the CMA, square root operations can be avoided at the price of additional square operations.…”
Section: Mean Modulus Algorithm (Mma) and Other Nonlinear Averages Fomentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the constant modulus algorithm (CMA) [15] is frequently used for polarization demultiplexing. In [2] and [13], it has been shown to also work for recovering frequency and timing information. The CMA cost function is defined by (16) is used as a cost function instead of the one for the CMA, square root operations can be avoided at the price of additional square operations.…”
Section: Mean Modulus Algorithm (Mma) and Other Nonlinear Averages Fomentioning
confidence: 99%
“…In particular, it is shown that our mean modulus algorithm (MMA) is well suited for both Nyquist and OFDM signals. It can be used to extract clock, carrier frequency and phase while featuring a low computational complexity [2] [13].…”
Section: Introductionmentioning
confidence: 99%
“…Optical OFDM has been a promising technology for next-generation optical communication systems due to its high spectral efficiency using high-order modulation enabling dynamic data rate adaptation [6][7][8][9][10][11][12]. Additionally, optical OFDM shows extreme robustness to fiber dispersion [6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…A number of synchronization techniques designed specifically for multi-gigabit per second optical OFDM have been developed in recent years [4][5][6][7][8]. Giddings et al [4] proposed overlaying a pattern of DC levels on OFDM symbols with a square waveform whose period is equal to the symbol length.…”
Section: Introductionmentioning
confidence: 99%